PERENCANAAN DAN PERANCANGAN PUSAT INDUSTRI KREATIF DI KABUPATEN BADUNG DENGAN PENDEKATAN DESAIN KONTEMPORER - I Wayan Ariawan; I Ketut Adhimastra; Anak Agung Ayu Sri Ratih Yulianasari (Jurnal Anala, 2024)
Structural development in the economy is not only about the use of natural resources but has now spread to the use of human resources. In the 1990s the internet entered Indonesia and until now in 2024, the internet has changed a lot in the way people communicate, even changing the way people trade and work. Countries in the world are competing to dominate international markets by developing technology and developing human resources. Under the leadership of the 7th President of the Republic of Indonesia, Indonesia is targeted to become a developed country in 2045. To support the ideals of the Indonesian state, human resources need to be prepared and trained to compete with countries in the world. Indonesia needs to develop a creative industry sector that utilizes skills, creativity and talent. The creative industry has a positive impact on cultural, social and educational preservation. Preparations need to be planned from the village level to the national level. Every region in Indonesia needs to have a creative industry center to support and stimulate the creativity of the country's creative children. This research will plan a creative industry center in Badung Regency, Bali Province. Badung Regency is the district that has the highest tourism visits. According to the creative economy agency, in 2021 there are 17 creative industry sub-sectors. Of the 17 existing sub-sectors, the creative center will facilitate 4 sub-sectors starting from applications, visual communication design, photography and advertising which will be planned to create an ecosystem that will collaborate with MSMEs. is in Badung Regency. The creative center will be planned with the aim of being a gathering place for startup players, as a place for education and recreation. The creative center in Badung Regency is planned in the form of a building which will be planned to facilitate the activities of 4 subsectors and MSMEs. The creative center building needs to be designed to be more developed in line with current design developments. The contemporary design concept is a concept that will be applied to creative industrial building planning because contemporary design is an architectural style that has developed according to the times